Lightweight aggregate fiber reinforced precast concrete material doped with gold tailing sand and preparation method of lightweight aggregate fiber reinforced precast concrete material

By using gold tailings sand and other industrial waste materials, combined with granulation technology and carbonization treatment process, high-strength, low-cost light aggregate fiber reinforced concrete is prepared, solving the high cost and poor toughness of existing lightweight concrete materials. The problem has achieved the goal of high performance and sustainable development.

CN119390408APending Publication Date: 2025-02-07HOHAI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411415577.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing lightweight concrete materials have high cost and poor toughness, which is difficult to meet the demand for high-performance and sustainable materials in the construction and transportation fields.

Method used

Gold tailings sand is used as aggregate, combined with waste glass powder, steel slag and fibers, and light aggregate fiber reinforced precast concrete materials are prepared through granulation technology and carbonization treatment process.

Benefits of technology

On the premise of ensuring mechanical properties, the production cost of concrete is reduced, the resource utilization of waste is realized, the tensile, bending and crack resistance of concrete is improved, and its toughness and sustainability are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079345940000091
    Figure BDA0005079345940000091
  • Figure BDA0005079345940000101
    Figure BDA0005079345940000101
Patent Text Reader

Abstract

The invention discloses a lightweight aggregate fiber reinforced precast concrete material doped with gold tailing sand and a preparation method. The concrete material is prepared from the following components in parts by weight: 200 to 300 parts of cement, 100 to 150 parts of fly ash, 150 to 200 parts of gold tailing sand, 75 to 100 parts of waste glass powder, 75 to 100 parts of steel slag, 1 to 4 parts of template agent, 5 to 10 parts of fiber, 10 to 15 parts of additive and 100 to 150 parts of water, wherein the template agent is put into water to prepare a template agent solution, the gold tailing sand, the waste glass powder and the steel slag are mixed and added into the template agent solution, the mixture is rolled in a granulator to prepare lightweight aggregate pellets, and the lightweight aggregate pellets are carbonized for use. The special lightweight aggregate and proportion are adopted, so that the concrete has the characteristics of the lightweight aggregate, is convenient to construct and transport, can be applied to building projects with strict requirements on the self weight of the structure, and reduces the production cost of the concrete to a certain extent by using wastes as part of raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of concrete materials, and in particular relates to a light aggregate fiber reinforced precast concrete material mixed with gold tailings sand and a preparation method thereof. Background Art

[0002] In the fields of construction and transportation, there is a growing demand for high-performance, sustainable materials. With the acceleration of urbanization and the continuous expansion of transportation infrastructure, traditional road slab materials are gradually facing challenges in terms of performance and environmental friendliness. For a long time, conventional concrete materials used in road construction have had problems such as heavy weight, complex construction, and limited durability. In order to reduce the weight of the structure, improve construction efficiency and reduce costs, the research and development of lightweight concrete materials has become a focus.

[0003] With the rapid development of economy, my country's demand for gold is growing. In recent years, my country's gold production has been increasing, and the yield has been growing, and it has gradually become a major gold-producing country. However, the gold content of gold mines is generally low, and a large amount of gold tailings will be produced during production. The solid waste generated in the gold beneficiation process exceeds 10 million tons each year, and the amount of waste increases year by year. The stacking of gold tailings is not only a waste of resources, but also has many hazards. If these tailings can be reasonably utilized, the problem of mine tailings storage can be solved to a certain extent, turning waste into treasure and creating economic benefits.

[0004] Taking into account the requirements of project cost and construction period, ultra-light fiber reinforced concrete (usually prepared from cement, silica fume, fly ash, slag powder and quartz sand) is usually used, which has super high compressive strength and durability. However, the raw materials for preparing ultra-light fiber reinforced concrete are mostly silicate cement, silica fume, quartz sand and high-efficiency water reducer, which makes the production cost of ultra-light fiber reinforced concrete more expensive, which is not conducive to the promotion and application of ultra-light fiber reinforced concrete. In ultra-light fiber reinforced concrete, gold tailings sand is used to replace quartz sand. This ultra-light fiber reinforced concrete has higher strength and other properties than ordinary strength concrete. Reasonable application of gold tailings can reduce various problems caused by tailings deposition and production, which is in line with the sustainable development supported by China in recent years. It can not only reduce the production cost of concrete, but also reduce the discharge of tailings ponds and reduce environmental pollution. The patent of CN116813373A discloses a lightweight aggregate concrete with high temperature stability and high strength and a preparation method thereof, which relates to the field of concrete design and preparation technology. The invention is composed of the following components in parts by weight: 500-700 parts of silicate cement, 125-175 parts of fly ash, 6.25-8.75 parts of steel fiber, 300-420 parts of hollow alumina spheres, 3-4.2 parts of water reducer, and 175-245 parts of water. It is based on silicate cement, with steel fiber fibers having the same thermal expansion coefficient as silicate cement as fiber reinforcement, and hollow alumina spheres with different particle gradations as light aggregate. The high-temperature resistant light aggregate concrete material prepared by combining other preferred mineral admixtures and additives solves the problem of poor high-temperature stability of concrete while reducing the concrete bulk density, and improves the application range of concrete materials in high-temperature extreme environments. The light aggregate hollow alumina spheres used are expensive, the manufacturing process is complicated, and the material cost is increased, which is not conducive to large-scale engineering applications. In addition, the invention patent only mentions compressive strength, and there is no tensile performance. CN113773014A discloses a gold tailings concrete and a preparation method thereof. The gold tailings concrete is prepared from the following raw materials: cement, slag powder, fly ash, mixed sand, fine stone, crushed stone, water, and a water reducing agent; the mixed sand is composed of the following components in weight percentage: 20-30% of gold tailings sand or hydrophobically modified gold tailings sand and 70-80% of river sand; in this solution, the gold tailings sand needs to be hydrophobically modified, which increases the processing cost. Summary of the invention

[0005] The purpose of the present invention is to provide a lightweight aggregate fiber reinforced precast concrete mixed with gold tailings to solve the problems of high cost and poor toughness of existing lightweight concrete. The ultra-light fiber reinforced concrete mixed with gold tailings of the present invention uses solid waste gold tailings as aggregate, and has a lower production cost while ensuring its mechanical properties.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand comprises the following components in parts by weight: 200-300 parts of cement, 100-150 parts of fly ash, 150-200 parts of gold tailings sand, 75-100 parts of waste glass powder, 75-100 parts of steel slag, 1-4 parts of template, 5-10 parts of fiber, 10-15 parts of admixture and 100-150 parts of water.

[0008] The template agent is at least one of analytically pure sodium dodecyl sulfate (SDS), sodium stearate and polyethylene glycol.

[0009] The template agent is preferably analytically pure sodium dodecyl sulfate.

[0010] Preferably, the gold tailings sand, waste glass powder and steel slag are mixed in a ratio of 2:1:1.

[0011] The template is put into water to prepare a 0.1-0.8 mol / L solution, gold tailings, waste glass powder and steel slag are mixed in a ratio of 2:1:1, the above solution is added, and small balls with a diameter of 5-10 mm are prepared by rolling in a granulator; these light aggregate small balls are then placed in a high-pressure reactor with a pressure of 0.1-0.3 MPa and a carbon dioxide concentration of 10-30% for carbonization treatment for 2-4 hours.

[0012] The selected cement is ordinary Portland cement with a strength grade not less than 42.5.

[0013] The selected fly ash is Class I fly ash, and its water demand ratio is not more than 95%.

[0014] The fineness modulus of the selected gold tailings sand is 2.0-2.5, and the mud content is no more than 2%.

[0015] The selected waste glass powder is clean and uniform, with an average particle size of less than 150 microns.

[0016] The selected steel slag is high-quality steel slag with a free calcium oxide content of less than 4%.

[0017] The selected fiber is PE fiber with a diameter of 25 μm, a length of 18 mm, and a breaking strength greater than 2600 MPa.

[0018] The selected admixture is a high-performance polycarboxylate water-reducing agent with a water reduction rate of not less than 20%.

[0019] A method for preparing a lightweight aggregate fiber reinforced concrete material mixed with gold tailings sand, the method comprising the following steps:

[0020] (1) The template is placed in water to prepare a 0.1-0.8 mol / L solution;

[0021] (2) Mix gold tailings, waste glass powder and steel slag in proportion and add the above solution, put them into a granulator and roll them to prepare lightweight aggregate balls with a diameter of 5-10 mm;

[0022] (3) placing the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor at a pressure of 0.1-0.3 MPa and a carbon dioxide concentration of 10-30% for carbonization treatment for 2-4 hours;

[0023] (4) Place cement, fly ash, lightweight aggregate balls and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes;

[0024] (5) Add water and water reducing agent and stir for 3-5 minutes;

[0025] (6) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0026] Step 4) The rotation speed of low-speed dry mixing is 50-100 rpm.

[0027] In step 6), the speed of high-speed stirring is 100-200 rpm.

[0028] The template concentration is 0.1-0.8 mol / L, preferably 0.2-0.5 mol / L. As the solution increases, the strength of lightweight aggregate and concrete continues to increase, and the water absorption rate decreases. After adding SDS, due to the generation of porous calcium carbonate, carbon dioxide can continuously enter through the pores and react with the raw materials to form a carbonization reaction, the degree of carbonization increases, and the strength of lightweight aggregate and concrete is further improved.

[0029] The carbonization conditions are preferably: carbonization pressure 0.2 MPa, carbon dioxide concentration 20%, and carbonization treatment for 3 hours.

[0030] The present invention utilizes gold tailings, waste glass powder, slag and other industrial waste materials, combined with granulation technology and carbonization treatment process, to prepare lightweight and high-strength lightweight aggregate. A template is added during the lightweight aggregate preparation process, which will guide the lightweight aggregate to generate porous calcium carbonate in the subsequent carbonization process, which is conducive to the carbonization reaction. This lightweight aggregate is applied to fiber-reinforced concrete materials to prepare lightweight, high-strength, and high-ductility new concrete materials.

[0031] The carbonization treatment process causes carbon dioxide (CO2) to react chemically with gold tailings, waste glass powder and slag to generate calcium carbonate (CaCO3) and silica gel. The calcium carbonate generated by the traditional carbonization method is dense calcite, which will wrap around the reactants, hinder the carbonization reaction, and reduce the carbonization efficiency of the reactants. The present invention adds a template to induce the generation of porous calcium carbonate during the carbonization process, which will not hinder the reaction, allowing the reactants to be carbonized continuously. At the same time, the generated product is also lightweight because of its porosity, which is conducive to the preparation of lightweight aggregate. The addition of fibers in the present invention has a reinforcing effect. When the concrete is subjected to external forces to produce microcracks, the fibers can span the cracks and withstand tension, thereby limiting the further development of the cracks and improving ductility.

[0032] In the present invention, unless otherwise specified, all preparation raw materials are preferably commercially available products well known to those skilled in the art.

[0033] Beneficial Effects

[0034] (1) Realize the resource utilization of waste: Use industrial waste such as gold tailings, waste glass powder, and steel slag as raw materials for concrete, which reduces the exploitation of natural resources, reduces the storage of waste and reduces pollution to the environment.

[0035] (2) Reduce the deadweight of concrete: By using special lightweight aggregates and mix proportions, concrete has the characteristics of lightweight aggregates, which is convenient for construction and transportation. At the same time, it can be applied to construction projects that have strict requirements on the deadweight of the structure.

[0036] (3) Improve concrete strength: The addition of fibers and the carbonization process enhance the tensile, bending and crack resistance of concrete, thereby improving the overall strength and stability.

[0037] (4) Reduce costs: Using waste as part of the raw materials can reduce the production cost of concrete to a certain extent. DETAILED DESCRIPTION

[0038] In order to further illustrate the present invention, the ultra-light fiber reinforced concrete mixed with gold tailings sand provided by the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0039] The cement is ordinary Portland cement with a strength grade of not less than 42.5, PO 42.5 cement;

[0040] The fly ash is Class I fly ash, and its water demand ratio is not more than 95%.

[0041] The fineness modulus of gold tailings sand is 2.0-2.5, and the mud content is no more than 2%.

[0042] The selected waste glass powder is clean and uniform, with an average particle size of less than 150 microns.

[0043] The selected steel slag is high-quality steel slag with a free calcium oxide content of less than 4%.

[0044] The selected fiber is PE fiber with a diameter of 25 μm, a length of 18 mm, and a breaking strength greater than 2600 MPa.

[0045] The selected admixture is a high-performance polycarboxylate water-reducing agent with a water reduction rate of not less than 20%.

[0046] Example 1 (no template added, no carbonization)

[0047] A light aggregate fiber reinforced concrete mixed with gold tailings consists of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings, 75 parts of waste glass powder, 75 parts of steel slag, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0048] Preparation method:

[0049] (1) Mix gold tailings, waste glass powder and steel slag in proportion, add a small amount of water and roll them in a granulator to prepare lightweight aggregate balls with a diameter of 5-10 mm;

[0050] (2) Put cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at a low speed of 80 rpm for 2-3 minutes;

[0051] (3) Add water and water reducing agent and stir for 3-5 minutes;

[0052] (4) Finally, the remaining fibers were added and stirred at a high speed of 150 rpm for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0053] Example 2 (without template)

[0054] A light aggregate fiber reinforced concrete mixed with gold tailings consists of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings, 75 parts of waste glass powder, 75 parts of steel slag, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0055] Preparation method:

[0056] (1) Mix gold tailings, waste glass powder and steel slag in proportion, add a small amount of water and roll them in a granulator to prepare lightweight aggregate balls with a diameter of 5-10 mm;

[0057] (2) The lightweight aggregate pellets prepared by the granulator are placed in a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 20% for carbonization treatment for 3 hours.

[0058] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes;

[0059] (4) Add water and water reducing agent and stir for 3-5 minutes;

[0060] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0061] Example 3

[0062] A light aggregate fiber reinforced concrete mixed with gold tailings sand is composed of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings sand, 75 parts of waste glass powder, 75 parts of steel slag, 1 part of analytically pure sodium dodecyl sulfate, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0063] Preparation method:

[0064] (1) Add analytically pure sodium dodecyl sulfate into water to prepare a 0.1 mol / L solution;

[0065] (2) mixing gold tailings, waste glass powder and steel slag in proportion and adding the above solution into a granulator to roll to prepare lightweight aggregate pellets with a diameter of 5-10 mm; placing the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 20% for carbonization treatment for 3 hours;

[0066] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes; (4) Add water and water reducing agent and stir for 3-5 minutes;

[0067] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0068] Example 4

[0069] A light aggregate fiber reinforced concrete mixed with gold tailings consists of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings, 75 parts of waste glass powder, 75 parts of steel slag, 1 part of sodium stearate, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0070] Preparation method:

[0071] (1) Sodium stearate was placed in water to prepare a 0.1 mol / L solution;

[0072] (2) mixing gold tailings, waste glass powder and steel slag in proportion and adding the above solution into a granulator to roll to prepare lightweight aggregate pellets with a diameter of 5-10 mm; placing the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 20% for carbonization treatment for 3 hours;

[0073] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes; (4) Add water and water reducing agent and stir for 3-5 minutes;

[0074] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0075] Example 5

[0076] A light aggregate fiber reinforced concrete mixed with gold tailings consists of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings, 75 parts of waste glass powder, 75 parts of steel slag, 1 part of polyethylene glycol, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0077] Preparation method:

[0078] (1) Put polyethylene glycol into water to prepare a 0.1 mol / L solution;

[0079] (2) mixing gold tailings, waste glass powder and steel slag in proportion and adding the above solution into a granulator to roll to prepare lightweight aggregate pellets with a diameter of 5-10 mm; placing the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 20% for carbonization treatment for 3 hours;

[0080] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes; (4) Add water and water reducing agent and stir for 3-5 minutes;

[0081] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0082] Example 6

[0083] A light aggregate fiber reinforced concrete mixed with gold tailings consists of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings, 75 parts of waste glass powder, 75 parts of steel slag, 2 parts of analytically pure sodium dodecyl sulfate, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0084] Preparation method:

[0085] (1) Add analytically pure sodium dodecyl sulfate into water to prepare a 0.2 mol / L solution;

[0086] (2) mixing gold tailings, waste glass powder and steel slag in proportion and adding the above solution into a granulator to roll to prepare lightweight aggregate pellets with a diameter of 5-10 mm; placing the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 20% for carbonization treatment for 3 hours;

[0087] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes; (4) Add water and water reducing agent and stir for 3-5 minutes;

[0088] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0089] Example 7

[0090] A light aggregate fiber reinforced concrete mixed with gold tailings sand is composed of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings sand, 75 parts of waste glass powder, 75 parts of steel slag, 4 parts of analytically pure sodium dodecyl sulfate, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0091] Preparation method:

[0092] (1) Add analytically pure sodium dodecyl sulfate into water to prepare a 0.4 mol / L solution;

[0093] (2) Mix gold tailings, waste glass powder and steel slag in proportion and add the above solution into a granulator for rolling to prepare lightweight aggregate pellets with a diameter of 5-10 mm; and place the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 20% for carbonization treatment for 3 hours.

[0094] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes;

[0095] (4) Add water and water reducing agent and stir for 3-5 minutes;

[0096] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0097] Example 8

[0098] A light aggregate fiber reinforced concrete mixed with gold tailings sand is composed of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings sand, 75 parts of waste glass powder, 75 parts of steel slag, 4 parts of analytically pure sodium dodecyl sulfate, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0099] Preparation method:

[0100] (1) Add analytically pure sodium dodecyl sulfate into water to prepare a 0.4 mol / L solution;

[0101] (2) Mix gold tailings, waste glass powder and steel slag in proportion and add the above solution into a granulator for rolling to prepare lightweight aggregate pellets with a diameter of 5-10 mm; and place the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.1 MPa and a carbon dioxide concentration of 20% for carbonization treatment for 3 hours.

[0102] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes;

[0103] (4) Add water and water reducing agent and stir for 3-5 minutes;

[0104] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0105] Example 9

[0106] A light aggregate fiber reinforced concrete mixed with gold tailings sand is composed of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings sand, 75 parts of waste glass powder, 75 parts of steel slag, 4 parts of analytically pure sodium dodecyl sulfate, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0107] Preparation method:

[0108] (1) Add analytically pure sodium dodecyl sulfate into water to prepare a 0.4 mol / L solution;

[0109] (2) Mix gold tailings, waste glass powder and steel slag in proportion and add the above solution into a granulator for rolling to prepare lightweight aggregate pellets with a diameter of 5-10 mm; and place the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 10% for carbonization treatment for 3 hours.

[0110] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes;

[0111] (4) Add water and water reducing agent and stir for 3-5 minutes;

[0112] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0113] Example 10

[0114] A light aggregate fiber reinforced concrete mixed with gold tailings sand is composed of the following raw materials in parts by weight: 200 parts of cement, 100 parts of fly ash, 150 parts of gold tailings sand, 75 parts of waste glass powder, 75 parts of steel slag, 4 parts of analytically pure sodium dodecyl sulfate, 5 parts of fiber, 10 parts of admixture and 100 parts of water.

[0115] Preparation method:

[0116] (1) Add analytically pure sodium dodecyl sulfate into water to prepare a 0.4 mol / L solution;

[0117] (2) Mix gold tailings, waste glass powder and steel slag in proportion and add the above solution into a granulator for rolling to prepare lightweight aggregate pellets with a diameter of 5-10 mm; and place the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 30% for carbonization treatment for 3 hours.

[0118] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes;

[0119] (4) Add water and water reducing agent and stir for 3-5 minutes;

[0120] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0121] For Example 1-10, a lightweight aggregate fiber reinforced concrete mixed with gold tailings sand was prepared according to the steps, and then demolded after curing at room temperature for 1 day, and placed in a high-temperature steam curing box at 80°C for 2 days of steam curing. The density and compressive strength of the lightweight aggregate and the density and tensile strength of the concrete were tested, and the test results are shown in Table 1.

[0122]

[0123]

[0124] The test results show that: Example 1-2 is a control group, Example 1 does not add a template and is not carbonized, and Example 2 does not add SDS, and the strength of the lightweight aggregate and the strength of the concrete are both low. After the template is introduced in Example 2-4, the strength of the lightweight aggregate is improved, the water absorption rate is reduced, and the strength of the concrete is also improved. Among them, SDS has the most obvious effect on improving the compressive strength of lightweight aggregate and concrete. This is because after adding SDS, due to the generation of porous calcium carbonate, carbon dioxide can continuously enter through the pores, react with the raw materials to carbonize, the degree of carbonization is increased, and the strength of lightweight aggregate and concrete is further improved. As the SDS concentration increases, the strength of lightweight aggregate and concrete continues to increase. The decrease in carbon dioxide concentration and pressure will cause the strength of lightweight aggregate and concrete to decrease. The concrete density of all embodiments is less than 1.9g / cm3. Therefore, it is feasible to prepare a lightweight aggregate concrete method using SDS and carbonization technology, and it is recommended to use the process described in Example 8.

[0125] Embodiment 11

[0126] A light aggregate fiber reinforced concrete mixed with gold tailings consists of the following raw materials in parts by weight: 250 parts of cement, 120 parts of fly ash, 170 parts of gold tailings, 85 parts of waste glass powder, 85 parts of steel slag, 4 parts of analytically pure sodium dodecyl sulfate, 8 parts of fiber, 12 parts of admixture and 130 parts of water.

[0127] Preparation method:

[0128] (1) Add analytically pure sodium dodecyl sulfate into water to prepare a 0.4 mol / L solution;

[0129] (2) Mix gold tailings, waste glass powder and steel slag in proportion and add the above solution into a granulator for rolling to prepare lightweight aggregate pellets with a diameter of 5-10 mm; and place the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.1 MPa and a carbon dioxide concentration of 20% for carbonization treatment for 3 hours.

[0130] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes;

[0131] (4) Add water and water reducing agent and stir for 3-5 minutes;

[0132] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0133] Example 12

[0134] A light aggregate fiber reinforced concrete mixed with gold tailings sand is composed of the following raw materials in parts by weight: 300 parts of cement, 150 parts of fly ash, 200 parts of gold tailings sand, 100 parts of waste glass powder, 100 parts of steel slag, 4 parts of analytically pure sodium dodecyl sulfate, 10 parts of fiber, 15 parts of admixture and 150 parts of water.

[0135] Preparation method:

[0136] (1) Add analytically pure sodium dodecyl sulfate into water to prepare a 0.4 mol / L solution;

[0137] (2) Mix gold tailings, waste glass powder and steel slag in proportion and add the above solution into a granulator for rolling to prepare lightweight aggregate pellets with a diameter of 5-10 mm; and place the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.2 MPa and a carbon dioxide concentration of 30% for carbonization treatment for 3 hours.

[0138] (3) Place cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes;

[0139] (4) Add water and water reducing agent and stir for 3-5 minutes;

[0140] (5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand, characterized in that: The concrete material comprises the following components in parts by weight: 200-300 parts of cement, 100-150 parts of fly ash, 150-200 parts of gold tailings, 75-100 parts of waste glass powder, 75-100 parts of steel slag, 1-4 parts of template, 5-10 parts of fiber, 10-15 parts of admixture and 100-150 parts of water; wherein the template is put into water to prepare a template solution, the gold tailings, waste glass powder and steel slag are mixed and added into the template solution, rolled in a granulator to prepare light aggregate pellets, and then the light aggregate pellets are used after being carbonized.

2. The lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand according to claim 1, characterized in that: The template agent is one of sodium dodecyl sulfate, sodium stearate and polyethylene glycol.

3. The lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand according to claim 1, characterized in that: The concentration of the template solution is 0.1-0.8 mol / L.

4. The lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand according to claim 1, characterized in that: The carbonization treatment conditions are: pressure 0.1-0.3 MPa, carbon dioxide concentration 10-30%, and carbonization treatment 2-4 hours.

5. The lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand according to claim 1, characterized in that: The fiber is PE fiber.

6. The lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand according to claim 2, characterized in that: The template agent is sodium dodecyl sulfate, and the concentration of the template agent solution is 0.2-0.5 mol / L.

7. The lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand according to claim 1, characterized in that: The fineness modulus of the gold tailings sand is 2.0-2.

5.

8. The lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand according to claim 1, characterized in that: The diameter of the lightweight aggregate pellets is 5-10 mm.

9. The method for preparing the lightweight aggregate fiber reinforced precast concrete material mixed with gold tailings sand according to any one of claims 1 to 8, characterized in that: The steps include: 1) The template is placed in water to prepare a 0.1-0.8 mol / L solution; 2) Mix gold tailings, waste glass powder and steel slag in proportion and add the above solution, put them into a granulator and roll them to prepare lightweight aggregate balls with a diameter of 5-10mm; 3) Place the lightweight aggregate pellets prepared by the granulator into a high-pressure reactor with a pressure of 0.1-0.3MPa and a carbon dioxide concentration of 10-30% for carbonization treatment for 2-4 hours; 4) Put cement, fly ash, lightweight aggregate and 2 / 3 of PE fiber into a mixer and dry mix at low speed for 2-3 minutes; add water and water reducing agent and stir for 3-5 minutes; 5) Finally, add the remaining fibers and stir at high speed for 5-10 minutes to obtain lightweight aggregate fiber reinforced concrete.

10. The preparation method according to claim 9, characterized in that: The low-speed stirring rate of step 4) is 50-100 rpm; the high-speed stirring rate of step 5) is 100-200 rpm.

Citation Information

Patent Citations

  • Gold tailing concrete and preparation method thereof

    CN113773014A

  • Lightweight aggregate concrete with high-temperature stability and high strength as well as preparation and application of lightweight aggregate concrete

    CN116813373A